2022
DOI: 10.26803/ijlter.21.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Rural STEM Preservice Teachers’ Acceptance of Virtual Learning

Abstract: Teaching and learning of Science, Technology, Engineering and Mathematics (STEM) to preservice teachers in rural universities has always been a challenge, resulting in poor student performance. The outbreak of COVID-19 has made it exacerbated this owing to lockdown restrictions in most institutions including universities. Consequently, universities switched to virtual learning (VL), even though most of them (especially rural universities) were not ready for it. This worsened the plight of struggling rural STEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The formation of a positive perception of teacher candidates can help knowledge, as an initial commitment to learning as a professional teacher (Kaban 2020;Kozikoğlu 2017). In line with Casebeer (2015) states that knowing the description of teaching and learning for teacher candidates makes the social process more dynamic. Visualizing the perspectives of teacher candidates can help them to construct positive concepts about teachers and teaching and learning practices (Yüksel 2019).…”
Section: Dwi Setyawan* and Wahyu Prihantamentioning
confidence: 96%
See 1 more Smart Citation
“…The formation of a positive perception of teacher candidates can help knowledge, as an initial commitment to learning as a professional teacher (Kaban 2020;Kozikoğlu 2017). In line with Casebeer (2015) states that knowing the description of teaching and learning for teacher candidates makes the social process more dynamic. Visualizing the perspectives of teacher candidates can help them to construct positive concepts about teachers and teaching and learning practices (Yüksel 2019).…”
Section: Dwi Setyawan* and Wahyu Prihantamentioning
confidence: 96%
“…Educational metaphors are widely used for educational practice and research, as one approach to explaining current educational practice (Casebeer 2015;Suleyman 2016;Wahyu et al 2021). The function of metaphor emphasizes profiling and mapping modeling mechanisms to understand individual competence and development (Soykan et al 2015).…”
Section: Dwi Setyawan* and Wahyu Prihantamentioning
confidence: 99%
“…Despite the fact that there have been a number of previous studies concerning the deve-loped STEM module with TAM implementation, the use of STEM module in the study of solar energy is still considered to be a novel implementation (Mutambara & Bayaga, 2021;Mater et al, 2022;Mutambara & Chibisa, 2022;Zhao et al, 2022). Some earlier research only addressed renewable energy in general, not solar energy specifically (Huenteler et al, 2016;Gu et al, 2019;Al-Janabi et al, 2020;Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the international literature has demonstrated that the target group is mostly comprised of university students (Goto, et al, 2021;Apandi, & Raman, 2020;Liu, & Yan, 2020), teachers (Tseng, et. al., 2022;Avcı, 2022), pre-service teachers (Fung, Smith, & Gandolfi, 2022;Mutambara, & Chibisa, 2022;Goto, Batchelor, & Lautenbach, 2021;Ning, & Dong, 2021;Bower, DeWitt, & Lai, 2020;Raman, & Don, 2013), and managers (Dakduk, et al, 2018). In addition, the topics include MOOCs (Tseng, et.…”
Section: Introductionmentioning
confidence: 99%